The Use of Discovery Learning in Improving Students’ Critical Thinking Ability - Trisna Dwi Jayanti, Ida Ayu Made (The Art of Teaching English as a Foreign Language (TATEFL), 2021)
Critical thinking ability is an essential ability that students need to compete in the 21 century. It is an ability to think carefully using reason and logic and being able to consider all the consequences of decisions taken to solve a problem. By having an ability to think critically, students are able to analyze and find solutions to any problems given by the teacher or problems they face in the real world. Students' critical thinking ability in Indonesia is still categorized as poor. Hence, teachers must find out the appropriate learning methods and models to train and improve students' critical thinking ability. This paper aims at identify the effectiveness of discovery-based learning model in improving students’ critical thinking ability. By then, teachers are expected to have an overview of how effective discovery-based learning is in improving students’ critical thinking ability.